Peran Teknologi Jaringan Pada Aplikasi Sistem DMS Terhadap Tingkat Penjualan Sparepart di PT. Dipo Internasional Pahala Otomotif - Suci Pajriana; Junidar Lorensia Telaumbanua (CV. ITTC INDONESIA, 2024)
The purpose of this article is to find out how important the role of internet network technology is in supporting operational activities in companies. The research object in this article is PT. Dipo Internasional Pahala Automotive uses internet network technology to run company system applications, namely DMS (Dynamic Master System). The DMS (Dynamic Master System) system application is useful for inputting, managing and storing important data or documents related to sales, purchases and all forms of company files related to the application. Testing was carried out using the Qualitative Descriptive method. Using a qualitative descriptive approach, this research explores the use of the DMS (Dynamic Master System) system in the sales department using interview survey techniques with respondents. The results show that internet network technology has a big influence on the company's operational activities, especially when inputting spare parts sales transactions. Where it often takes a long time to input customer spare part sales due to frequent buffering or unstable internet network conditions, so innovation must be carried out in the company's system application by implementing features that can facilitate the spare part sales process and can increase company profits.